Foreign bank entry and firms’ access to bank credit: Evidence from China - Lin, Huidan (Journal of Banking & Finance, 2011)
This paper studies the impact of foreign bank entry on domestic firms’ access to bank credit using a within-country staggered geographic variation in the policy of foreign bank lending in China. The paper finds that after foreign bank entry profitable firms use more long-term bank loans; whereas firms with higher value of potential collateral do not. It also finds that non-state-owned firms become able to substitute some trade credit with long-term bank loans. The findings suggest that less opaque firms and non-state-owned firms benefit more from foreign bank entry and that collateral may only play a limited role in mitigating the problem of information asymmetry when creditors’ rights are not well protected in a host country.